Surface Selective 1H and 27Al MAS NMR Observations of Strontium Oxide Doped γ-Alumina. Issue 2 (1st April 2016) - Barrow, By Nathan S.; Scullard, Andrew; Collis, Nicola
High-surface area γ-alumina is industrially used as a catalyst support. Catalytically active elements are doped onto the support, where they can bind to AlO4, AlO5 or AlO6 sites on the surface. Pretreating the surface with alkaline earth oxides can alter the availability of these surface sites, hence affecting the catalytic activity. The surface binding sites of strontium oxide (SrO) on γ-alumina were previously unknown. Direct 27Al magic angle spinning nuclear magnetic resonance (MAS NMR) could not detect AlO5 sites at 9.4 T, so 1H‐27Al cross-polarisation (CP) MAS NMR was used to preferentially select the surface environment signals. We directly observed the three surface environments on dehydrated γ-alumina as a function of SrO impregnation up to 4 wt% SrO. We found that Sr2+ preferentially binds to AlO5 and AlO6 surface sites. 1H MAS NMR revealed SrO impregnation causes a reduction in the terminal (−0.3 ppm) and bridging (2.2 ppm) hydroxyl environments, as well as the promotion of a new peak in between these sites, at 0.5 ppm. By using 1H‐27Al CP/MAS NMR the relative proportions of surface sites on γ-alumina can be determined, allowing an optimal level of SrO doping that can saturate all the AlO5 sites. Importantly, this provides a method of subsequently depositing catalytically active elements on just the AlO4 or AlO6 sites, which can provide a different catalytic activity or stability compared to the AlO5 binding site.